2022
DOI: 10.1093/bjs/znac196
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative care bundles for the prevention of surgical-site infections: meta-analysis

Abstract: Background Care bundles are used widely to prevent surgical-site infections (SSIs). Recent systematic reviews suggested larger effects from bundles with more interventions. These reviews were largely based on uncontrolled before–after studies and did not consider their biases. The aim of this meta-analysis was to determine the effectiveness of care bundles to prevent SSIs and explore characteristics of effective care bundles. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…First, the evidence-based performance measures in this study are highly recommended by most guidelines and should be recommended for all surgical procedures [ 1 , 3 , 6 ]. However, the risk factors of SSI are complex and multifactorial [ 3 , 6 , 12 ], and this study did not analyze all the perioperative risk factors. Second, a meta-analysis has indicated that the effect of perioperative care bundles for the prevention of SSIs is inconsistent across randomized control trials [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the evidence-based performance measures in this study are highly recommended by most guidelines and should be recommended for all surgical procedures [ 1 , 3 , 6 ]. However, the risk factors of SSI are complex and multifactorial [ 3 , 6 , 12 ], and this study did not analyze all the perioperative risk factors. Second, a meta-analysis has indicated that the effect of perioperative care bundles for the prevention of SSIs is inconsistent across randomized control trials [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk factors of SSI are complex and multifactorial [ 3 , 6 , 12 ], and this study did not analyze all the perioperative risk factors. Second, a meta-analysis has indicated that the effect of perioperative care bundles for the prevention of SSIs is inconsistent across randomized control trials [ 12 ]. No strong evidence for the characteristics of effective preventive care bundles was identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4–6 The number and type of measures included in a SSI bundle can vary considerably, but some measures are mentioned more often. 7 These measures are focused on surgical-site preparation, hair removal, antibiotic prophylaxis, wound closure, normothermia and glycaemic control. 7–10 …”
Section: Introductionmentioning
confidence: 99%